2016
DOI: 10.1016/j.socscimed.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Bisexuality, poverty and mental health: A mixed methods analysis

Abstract: Bisexuality is consistently associated with poor mental health outcomes. In population-based data, this is partially explained by income differences between bisexual people and lesbian, gay, and/or heterosexual individuals. However, the interrelationships between bisexuality, poverty, and mental health are poorly understood. In this paper, we examine the relationships between these variables using a mixed methods study of 302 adult bisexuals from Ontario, Canada. Participants were recruited using respondent-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 27 publications
1
50
1
1
Order By: Relevance
“…Research has consistently identified higher levels of poverty among bisexual and other non-monosexual groups in contrast to their monosexual peers (Gorman, Denney, Dowdy, & Medeiros, 2015;Ross et al, 2016). Poverty and income inequality may then be considered a social justice issue for individuals under the umbrella, and the greater number of people advocating for income equality, the more likely our voices are to be heard.…”
Section: Bisexual Umbrella Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has consistently identified higher levels of poverty among bisexual and other non-monosexual groups in contrast to their monosexual peers (Gorman, Denney, Dowdy, & Medeiros, 2015;Ross et al, 2016). Poverty and income inequality may then be considered a social justice issue for individuals under the umbrella, and the greater number of people advocating for income equality, the more likely our voices are to be heard.…”
Section: Bisexual Umbrella Benefitsmentioning
confidence: 99%
“…Another uniting factor among the wide range of people included under the umbrella is the higher vulnerability for negative health outcomes (Schick & Dodge, 2012), which is also related to income inequality (Braveman, Egerter, & Williams, 2011;Ross et al, 2016). Whether nonmonosexuality is categorized by identity or behavior, researchers consistently report higher rates of negative mental and physical health outcomes among nonmonosexual people in contrast to our monosexual peers, though how nonmonosexuality is conceptualized within research affects the overall outcomes (Bauer & Brennan, 2013).…”
Section: Bisexual Umbrella Benefitsmentioning
confidence: 99%
“…In such a context, the gay subject cannot make proper sense of his sexuality, owing to the fact that gay people as such were prevented from making a full contribution to collective resources for social meaning, with the result that the forms of understanding available for making sense of homosexuality were crucially uninformed and distorted. (p. 70) Similarly, bisexuals can experience testimonial and hermeneutical injustice in society (e.g., Bostwick & Hequembourg, 2014;Ross et al, 2010;2016;Sarno & Wright, 2013, which may be addressed through various methods in social work research and practice).…”
Section: Epistemic Injusticementioning
confidence: 99%
“…These epistemic injustices vis-a`-vis microagressions may help explain why bisexuals have the highest rates of mental health issues among sexual minorities (King & McKeown, 2003;Jorm et al, 2002) and why they have uniquely negative experiences within the healthcare system (Dobinson et al, 2005). For instance, because of bisexual invisibility, many healthcare providers, including LGBTQ-friendly providers, are not always competent regarding bisexuality and are perceived by bisexuals as not inclusive of their identity and reality (Dobinson et al, 2005;Ross et al, 2010;2016). Bisexuals can also experience judgment or dismissiveness about their sexual identity from health care providers and social workers, as well as inappropriate questions about their sexual practices (Eady, Dobinson, & Ross, 2011).…”
Section: Linking Epistemic Injustice To Microagressionsmentioning
confidence: 99%
“…Em relação à baixa percepção de suporte social em relação aos bissexuais, esta pode estar relacionada ao baixo nível socioeconômico desta população, o que, para Ross et al (2016), está fortemente ligado aos maus resultados de saúde mental e ao estresse pós-traumático, os quais são agravados pela discriminação, pela falta de apoio social e pela inacessibilidade financeira aos serviços de apoio (GORMAN et al, 2015).…”
Section: Gir 2016)unclassified